Una nueva especie del género Pristimantis (Anura: Craugastoridae) del complejo de páramos Merchán-Iguaque (Boyacá, Colombia) (2015)
During an exploratory field trip, made to identify possible study areas in one of the isolated paramos north of the Arcabuco region (Boyacá, Colombia), a species of terrestrial frog assignable to the unistrigatus species group of the genus Pristimantis was discovered. It is similar in morphology to the species group with reduced discs formed by Pristimantis mnionaetes, P. nervicus and P. nicefori of the Cordillera Oriental of Colombia. These species allow the recognition of 10 species of this genus associated with high mountain environments in the Eastern Cordillera of Colombia. Data on their morphology, distribution and natural history and associated anurans reported from this geographical area are presented.